A Strategy for Management of Sustainable Water Supply System in Rural Areas - Rusdiana Setyaningtyas Wachid (Jurnal Teknik Lingkungan, 2022)
The sustainability of rural drinking water supply systems (SPAM) is an important development issue in Indonesia related to the low access to clean and healthy water in rural areas. The low level of drinking water service in rural areas is inseparable from the failure of drinking water development which is caused by the absence of an optimal rural drinking water supply system. As happened in post-Pamsimas villages in Jember Regency. This condition is the background for researchers in conducting studies to find out what factors affect the sustainability of the use of SPAM facilities and infrastructure that are built, especially from the Pamsimas program based on the fulfillment of the KPI (Key Performance Indicator) target, namely KPI 3 related to the management of "sustainable service provision. drinking water for the community ”. This study aims to (1) identify the causes for the inadequate sustainability of rural SPAM management in Jember Regency, (2) analyze internal and external factors that affect the sustainability of rural SPAM in Jember Regency, and (3) determine a sustainable strategy for the management of the drinking water supply system. villages that are in accordance with existing conditions in Jember Regency based on case studies in 19 villages after Pamsimas FY 2017. The research analysis used qualitative and quantitative descriptive and SWOT analysis. The results showed (1) the management of rural SPAM in Jember Regency has not been optimal with the fulfillment of the KPI target in 3 villages after Pamsimas FY 2017 is still 78.95% (<90%), (2) the weighted score of the EFAS and IFAS Matrix (or IE Matrix) results analysis of internal and external factors are (0.30; 0.76), (3) to ensure the sustainability of rural SPAM management in Jember Regency, the SO (Strengths - Opportunities) strategy can be used, namely strategies to achieve policy objectives by utilizing strengths and potentials/opportunities owned through cooperation and partnerships with stakeholders (Pemdes, Pemda, Higher Education, private sector, banking) as well as the beneficiary community.